Proteomic Analysis of Non-human Primate Peripheral Blood Mononuclear Cells During Burkholderia mallei Infection Reveals a Role of Ezrin in Glanders Pathogenesis - Chiang, Chih-Yuan; Zhong, Yang; Ward, Michael D.; Lane, Douglas J.; Kenny, Tara; Rosario-Acevedo, Raysa; Eaton, Brett P.; Treviño, Sylvia R.; Chance, Taylor B.; Hu, Meghan; Worsham, Patricia L.; Waag, David M.; et al. (Frontiers in Microbiology, 2021)
Burkholderia mallei, the causative agent of glanders, is a gram negative intracellular bacterium. Depending on different routes of infection, the disease is manifested by pneumonia, septicemia, and chronic infections of the skin. B. mallei poses a serious biological threat due to its ability to infect via aerosol route, resistance to multiple antibiotics and the lack of vaccines. Induction of innate immunity and inflammatory cytokines and chemokines following B. mallei infection, have been observed in in vitro and small rodent models; however, a global characterization of host responses has never been systematically investigated using a non-human primate (NHP) model. Here, using a liquid chromatography-tandem mass spectrometry (LC-MS/MS) approach, we identified host proteins whose expression levels were altered in peripheral blood mononuclear cells (PBMCs) originating from naïve Rhesus macaques (Macaca mulatta), African green monkeys (Chlorocebus sabaeus) and Cynomolgus macaques (Macaca fascicularis) exposed to aerosolized B. mallei. Gene ontology (GO) analysis identifies several statistically significant overrepresented biological annotations including complement and coagulation cascade, nucleoside metabolic process, vesicle-mediated transport, intracellular signal transduction and cytoskeletal protein binding. By integrating an LC-MS/MS derived proteomics dataset with a previously published B. mallei host-pathogen interaction dataset, a statistically significant predictive protein-protein interaction (PPI) network was constructed. Pharmacological perturbation of one component of the PPI network, specifically ezrin, reduced B. mallei mediated interleukin-1β (IL-1β). On the contrary, the expression of IL-1β receptor antagonist (IL-1Ra) was upregulated upon pretreatment with the ezrin inhibitor. Taken together, inflammasome activation as demonstrated by IL-1β production and the homeostasis of inflammatory response is critical during the pathogenesis of glanders. Furthermore, the topology of the network reflects the underlying molecular mechanism of B. mallei infections in the NHP model